Chlorhexidine with an Anti Discoloration System. A comparative study - F Bernardi (Journal compilation 2007 Blackwell Munksgaard, 2007)
Correct oral hygiene is believed to be the basis of primary and secondary prevention. Sometimes, using a toothbrush or other mechanical instruments for oral hygiene may be difficult and it may become necessary to use an antiseptic.